The effects of stakeholder pressure on eco-innovation practices in Malaysian chemical industry - Omar, Salmah; Othman, Norfaridatul Akmaliah (INSInet Publications, 2016)
Background: Environmental activities are increasingly seen as a potential source of competitive advantage.Malaysia also realized investing in environmental protection becomes increasingly important.The term environmental innovation or eco-innovation relates to innovations aiming at a decreased negative influence of innovations on the natural environment. Thus, it is important to identify the processes and agenda governing the development of the sustainability of an organization.It is therefore vital to understand what motivates companies to implement eco-innovation practices as environmentally friendly solutions.Objective: In this study, the conceptual framework is proposed and tested between stakeholder pressure (SHP) and eco-innovation practices (EIP). Results: EIP is influenced directly by SHP (β=0.390, t=3.686, p<0.000).Conclusion: The findings of this study reveal that stakeholder pressure (SHP) is an important antecedence in affecting eco-innovation practices. This variable concerns receiving pressure from government, especially local government, environmental and enforcement agencies, and national legislator will influence the extent of eco-innovation practices implementation.